Efektivitas Penggunaan Model Pembelajaran Kooperatif Tipe Student Team Achievment Division (STAD) Terhadap Hasil Belajar Pekerjaan Dasar Otomotif (PDO): Efektivitas Pengunaan Model Pembelajaran Kooperatif Tipe Student Team Achievement Division (STAD) Terhadap Hasil Belajar Pekerjaan Dasar Otomotif (PDO) - Galih Sulisya Bagaskoro; Subagyo Subagyo; Arif Bintoro Johan (Program Studi Pendidikan Vokasional Teknik Mesin, Universitas Sarjanawiyata Tamansiswa, 2022)
The research objective descriptively was to determine the trend of PDO learning outcomes where the learning used the Student Team Achievement Divisions model and conventional models and to determine the differences in the PDO learning outcomes where the learning used the Student Team Achievement Divisions model and conventional models. This type of research is a quasi experiment. Methods of data collection using tests and documentation. The research instrument was a test. The data analysis technique used descriptive analysis, the hypothesis test used the t test which was preceded by the distribution normality and variance homogeneity tests. The results of the descriptive study show that the learning outcomes of the PDO which are taught using the Student Team Achievement Divisions model are classified as very high with a mean value of 19,000 and the conventional model is classified as high with a mean value of 14,412. Comparatively, there are differences in the learning outcomes of the PDO where learning uses the Student Team Achievement Divisions model and the conventional model with a value of thit = 3,926 and a value of p = 0,000 <0.05. By looking at the average automotive basic work learning outcomes using the Student Team Achievement Division 19,000 learning model and using the conventional learning model 14,412, the Student Team Achievement Division learning model has more influence on the learning outcomes of automotive basic work compared to conventional models.